Knowledge, Attitude and Practice of Menstrual Hygiene among High Schools Students in Jatinangor - Balqis, Maryam; Arya, Insi Farisa Desy; Ritonga, Mulya Nusa A (Althea Medical Journal, 2016)
Background: Menstruation is a physiological process in female adolescents which usually started at age of 9â12 years. Menstrual hygiene is a hygienic practice during menstruation which can prevent women from the infection in reproductive and urinary tract. Lack of knowledge regarding menstruation and menstrual hygiene lead to poor attitude and practice. This study was conducted to assess the level of knowledge, attitude and practice of menstrual hygiene among high schools students in Jatinangor.Methods: This descriptive cross-sectional study was conducted from May until June 2013 in high schools around Jatinangor. This study population was taken from four schools selected through cluster random sampling from 17 junior and senior high schools available in Jatinangor. Total sampling from four schools was undertaken and a total of 238 female high school studentsâ data were established. The respondents aged between 13â19 years old.Results: The level of knowledge, attitude and practice among participants were 180 (75.63%), 186 (78.15%) and 210 (88.24%) respectively which were mostly good. Conclusions: Overall, most of the participants in this study have good knowledge, attitude and practice about menstrual hygiene, but a few of them still have poor and moderate knowledge and attitude, although there is no poor practice among them. [AMJ.2016;3(2):230â8]Â DOI:Â 10.15850/amj.v3n2.783